Programs for Improvement of Medicago spp. at ENMP-Portugal. I. Distribution of annual medics as related to soil properties and climatic conditions - Carneiro J.P.; Serrão M.G. (The Genus Medicago in the Mediterranean region: Current situation and prospects in research, 1996)
More than 100 entries of Medics were collected during three seed collection tours undertaken in the Centre and South regions of Portugal. Some soil properties and climatic conditions at collection sites were studied, and the species identification was done. The results of identification and environmental characterization showed the relevance of Medicago polymorpha as the most frequent and cosmopolitan species. Some species more adapted to low soil pH and reduced availability of some major elements were identified.
Meeting of the Mediterranean Working Group on Medicago of the FAO/CIHEAM Inter-Regional Research and Development Network on Pastures and Fodder Crops, 1995/10/19-22, Hammamet (Tunisia)